Applying Participatory Action Research Methods in Community-Based Adaptation With Smallholders in Myanmar - Barbon, Wilson John; Myae, Chan; Vidallo, Rene; Thant, Phyu Sin; Monville-Oro, Emilita; Gonsalves, Julian (Frontiers in Climate, 2021)
The effects of climate change to agriculture being location specific, it is crucial that adaptation measures recognize the value of targeted, context specific, community-based strategies and processes. This research seeks to demonstrate participatory action research as applied in the climate smart village approach by using different socio-technical methodologies, for facilitating community level adaptation in smallholder farms in four unique agro-ecologies in Myanmar. We present the experiences, results and insights from a 3-year participatory action research highlighting how the climate smart village approach was optimized and implemented in the four CSVs as well as the key support systems that are needed in bringing effective community engagement in implementing the CSVs. We also used social learning at the CSV level where community members assess and generate learning towards improving the adaptation options identified and tested. Social learning is to aimed at nurturing the capacity of farmers to find solutions, testing and improving them. Using a combination of socio-technical processes we allowed smallholder farmers, researchers and facilitators to understand the experiences of climate change, the drivers of vulnerability and coping activities. Using this shared knowledge and understanding, the CSVs identified a menu of adaptation options to test and scale based on evidence. This “portfolio approach” to adaptation options ensured that there are opportunities for men, women including landless households to participate in the community adaptation process. Our analysis of the land tenure regimes influences the nature of the adaptation options and their eventual uptake . In villages with high incidence of landlessness, the adaptation options are limited to homesteads, the small patch of land around the household dwelling. A more secure tenure status gives more freedom to engage in diversified and long-term production systems. Poverty and wealth levels of the households are also factors in the uptake of adaptation options especially in diversifying production, thereby spreading risks.